Biology of Horadandia atukorali Deraniyagala 1943 (cyprinidea:teleostei) : Ornamental fish of the Western Ghats of India - Seena Augustine P A (kufos, 2016)
Abstract- Horadandia atukorali, Deranyagala, 1943 is a small cyprinid (danionid) fish distributed in southern India and Sri Lanka, which is an indigenous ornamental fish of the Western Ghats of India.